Determination of digoxin serum level in patients with heart failure: digoxin serum level and heart failure - Li, Qiang; Wu, Guanghang; Lu, Ping (Cellular and Molecular Biology, 2022)
Heart failure is one of the common cardiovascular diseases, and digoxin is required in the list of drug treatments. Considering the positive effect of this drug on heart failure, unfortunately, its therapeutic and toxic serum levels are different and very close to each other in different people. This study aimed to investigate the digoxin serum level in heart failure patients. For this purpose, we examined 32 patients with heart failure and digoxin users in this cross-sectional descriptive study. Some important factors involved in determining digoxin toxicity, such as age, gender, creatinine, creatinine clearance, cardiac output, urea, potassium, calcium, and digoxin levels, were measured. Statistical analysis showed that digoxin serum level increases with age (p<0.01). The increase in digoxin serum level was related to urea, creatinine, and potassium serum levels (p<0.01). In general, it seems that to prevent the increase of digoxin serum level and poisoning with it, it is necessary to continuously control the serum level of this drug in the form of serum measurement or according to its clearance.